1983
DOI: 10.1007/bf01800730
|View full text |Cite
|
Sign up to set email alerts
|

A case of pyruvate carboxylase deficiency with later prenatal diagnosis of an unaffected sibling

Abstract: A severely mentally retarded infant with congenital lactic acidosis due to pyruvate carboxylase deficiency is reported. The patient suffered from vomiting and convulsions soon after birth and developed severe mental and motor retardation at 3 months of age. The persistent elevation of pyruvate and lactate in both blood and cerebrospinal fluid and hyperalanaemia suggested an impairment of pyruvate oxidation. The enzyme activities of pyruvate carboxylase in both liver tissues and cultured skin fibroblasts of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This contrasts with pyruvate dehydrogenase complex deficiency [Shevell et al, 1994] and the A form of PC deficiency in which progressive microcephaly is observed [Atkin et al, 1979;Tsuchiyama et al, 1983]. The neuropathology of PC deficiency is similar to that of other mitochondrial diseases: spongiform degeneration, neuronal loss, gliosis, and delayed myelination can be found [Brown and Squier, 1996].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This contrasts with pyruvate dehydrogenase complex deficiency [Shevell et al, 1994] and the A form of PC deficiency in which progressive microcephaly is observed [Atkin et al, 1979;Tsuchiyama et al, 1983]. The neuropathology of PC deficiency is similar to that of other mitochondrial diseases: spongiform degeneration, neuronal loss, gliosis, and delayed myelination can be found [Brown and Squier, 1996].…”
Section: Discussionmentioning
confidence: 88%
“…Previously reported anomalies of skeletal muscle fibers in PC deficiency emphasized excess amounts of lipid droplets [DeVivo et al, 1977;Atkin et al, 1979;Tsuchiyama et al, 1983], which likely reflected a metabolic shunt due to under use of the TCA cycle acetyl-CoA recruited for lipid synthesis [Oizumi et al, 1986]. Intermyofibrillary proliferation of mitochondria in the heart has only been documented once [Rutledge et al, 1989].…”
Section: Discussionmentioning
confidence: 97%
“…Following the description of measurable levels of PC in cultured amniocytes (Feldman and Wolf, 1979), there have been two reports of prenatal diagnosis in families at risk. The first reported an affected fetus with enzyme analysis carried out in four centres (Marsac et al, 1982) and the second an unaffected fetus (Tsuchiyama et al, 1983).…”
Section: Introductionmentioning
confidence: 99%